HUBUNGAN PENGETAHUAN IBU GURU TENTANG MAKANAN PENDAMPING ASI (MP-ASI) DENGAN STATUS GIZI BAYI USIA 6-12 BULAN DI KECAMATAN PAKKAT KABUPATEN HUMBANG HASUNDUTAN - Riana Friska Siahaan; Santi Sihotang (JURNAL KELUARGA SEHAT SEJAHTERA, 2015)
ABSTRACT This study aims to determine: (1) knowledge of the teachers about complementary foods (solids) of 6-12 months baby in the village of the District Pakkat Pakkat Humbang Hasundutan. (2) The nutritional status of infants aged 6-12 months in District District Pakkat Humbang Hasundutan. (3) The relationship between teacher knowledge about complementary foods (solids) and the nutritional status of infants aged between 6-12 months in District Pakkat Humbang Hasundutan. The study’s populations were 94 people and the research sample of 33 people, this study used purposive sampling technique. Prior to this research, first trials were conducted in the District Tarabintang was to test the validity and reliability. The results of trials testing on  the mother's knowledge about complementary foods ASII teachers from 40 grains invalid test is 5 points so to collect data used 35 studies with a reliability test items included in the category 1.01634271 very high. Test requirements analysis is a test of normality and linearity test. Normality test results shows that the distribution of all data variables with normal distribution in this study, which tested using chi-square test. Alteration of data normality test results (X) with degrees of freedom (df = k-1). At the 5% significance level turns x2hitung < x2tabel or 2.75 < 11,070, thus it can be stated that the data variables teacher knowledge about complementary feeding normal distribution, and alteration of data normality test (Y) with degrees of freedom (df = k-1 ) at the significant level of 5% turned out x2hitung < x2tabel or 11.01 < 11,070. Thus it can be stated that the data variables Nutritional Status of infants aged 6-12 months (Y) distributed normal. Result hypothesis testing shows rtable value at significance level of 5% with degrees of freedom df = N = 40 is 0344. Thus rxy> rtabel is 0723 > 0312 so that the simple correlation coefficient reveals meaningful. With the results obtained knowledge The teacher who was, so the hypothesis is acceptable and in line with the results of the study that there is a positive relationship between knowledge and means Teacher About Food Companion (solids) with the nutritional status of infants aged 6-12. Kata Kunci : Pengetahuan ibu guru tentang makanan pendamping , status gizi